CRISPR-based screening identifies the role of KRAB-containing transcription factors ZIM3 and ZNF394 in human major zygotic genome activation - Jiayu Li; Liangfu Xie; Cheng Shi; Tiantian Zhang; Xiwen Lin; Haokun Da; Kongqianqian Sun; Chunsheng Han; Bing Zhu; Xi Chen; Hongkui Deng; Jun Xu (Cell Reports)
Summary: The initiation of major zygotic genome activation (ZGA) is crucial for human early embryogenesis. However, the transcription factors (TFs) regulating major ZGA in humans remain largely unknown. Here, we performed a CRISPR-based activation screen of 1,603 human TFs in human extended pluripotent stem cells (hEPSCs), which identified 132 candidates as potential regulators of major ZGA. Further evaluation of these candidates revealed that the KRAB-containing TFs ZIM3 and ZNF394 activated totipotent features in hEPSCs upon overexpression. Importantly, simultaneous knockdown of these two TFs arrested human embryo development prior to the eight-cell embryo stage. Mechanistically, the KRAB domains contributed to ZIM3- and ZNF394-mediated totipotency induction in vitro, accompanied by the suppression of a set of four-cell embryo enriched genes. Our study provided valuable resources for totipotency and major ZGA regulation, suggesting an un-reported role of KRAB-containing TFs in major ZGA in humans.